Analisis Pengembangan Sumber Daya Manusia Lion Air dalam Perspektif Digital Empowermennt: Penelitian - Nur Fattah Riski Harahap; Hendra Riofita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the human resource development strategy at Lion Air from the perspective of digital empowerment. The research applies a qualitative descriptive method through a literature study based on several sources, including Hendra Riofita’s journals which highlight the role of digital empowerment in improving organizational performance. The results indicate that Lion Air implements HR strategies focusing on enhancing employees’ digital competencies through training, technology-based evaluation systems, and the strengthening of adaptive work culture. The implementation of digital empowerment has been proven to improve operational efficiency, productivity, and service quality. This study emphasizes the importance of digital transformation in human resource management to meet the challenges of the modern aviation industry.